Dendritic cells: phenotypic and functional heterogeneity - Silvano, Angela (Italian Journal of Anatomy and Embryology, 2015)
Dendritic cells are specialized to capture antigens, process them and present them to T cells to initiate, regulate and fine tune immune responses towards pathogens and tumours. The story of these cells began more than forty years ago and the interest for them is ever growing because of their central role in immunobiology. Dendritic cells are heterogeneous for origin, anatomical localization, phenotype and function: several subsets of myeloid dendritic cells and plasmacytoid dendritic cells have been recognized until now. Dendritic cells differentiate from haematopoietic stem cells-derived precursors, migrate from sites of antigen uptake to lymphoid organs and during this process mature to antigen presenting cells capable of interacting with lymphocytes and stimulate both immune response and peripheral tolerance to self. Since dendritic cells play crucial roles in infection, cancer, allergy, autoimmunity and graft rejection, thorough knowledge of their subsets and behaviour will open the path to tools allowing better control of many clinical conditions.